Arcturus – Design och konstruktion av en vektorstyrd modellraket - Bergstedt, Frode; Eklind, Tilde; Enell, Anton; Gustafsson, Victor; Randerz, Viggo; Richardt, Christian (My University, 2026)
The goal of the project was to design and build a thrust vector controlled (TVC) model rocket, with an aim to stabilize the rocket with active control. The aim was split into three parts: (1) simulation; (2) static test with free rotation; and (3) free launch. To comply with Swedish laws, the rocket was restricted to maximum weight of 500 g, with a maximum 100 g reserved for propellant. With these design limitations in mind, the rocket body and systems for both the electronics, TVC, and parachute were custom made, with the goal to minimize weight. The designed rocket weighed a total of 499,2 g with propellant. However, parts like the custom flight computer did not work as intended, thus a new makeshift solution was required for launch. After the rocket was designed and built, three static test launches and one live flight were executed. Even though the simulations gave promising results, none of the launches proved successful. This could be due to a discrepancy between simulation and reality. In the end, the goal was achieved, but the aim failed on all three parts, which could have been remedied by a longer research and development phase.
Keywords: Thrust Vector Control (TVC); Model Rocketry; Active Stabilization; Aerospace Engineering; Additive Manufacturing; Generative Design; Flight Dynamics Simulation; Control Theory; Prototyping; Embedded Systems